Success Factors in R&D Leadership: Leadership Skills and Attributes for R&D ManagersAnalysis of data from a large-scale survey reveal the behaviors, skills, and attributes that distinguish successful R&D leaders. Issue 4 (4th July 2017) - Gritzo, Louis; Fusfeld, Alan; Carpenter, Dan
OVERVIEW: A wealth of information and research is available about business leadership in general and its importance, but much less attention has been given to the nature of R&D leadership specifically. Given the importance of innovation to most organizations' success, and even survival, understanding the skills and attributes required to achieve success in R&D management is critical. To address this gap, IRI's Research-on-Research working group R&D Leadership Skills and Styles sought to both identify leadership skills and attributes important to R&D success and to assess the relative importance of known leadership attributes for R&D compared to other business units. After identifying key themes in innovation leadership through a series of interviews with established technical leaders, the group embarked on comprehensive analyses of data from CCL leadership survey instruments to explore these themes. The analyses reveal a general perception that R&D managers are typically not as effective as those outside R&D on the majority of leadership skill measures, except in a small number of areas, most of which are technical. Further analysis of the interview trends and data suggests unique opportunities to develop successful R&D leaders by maintaining technical insight while expanding interpersonal skills. In other areas, R&D leaders would be well served by work to develop the leadership skills and attributes identified as generally important, as they are widely perceived as lacking a number of these attributes.